Sperm Nuclear DNA in Ejaculates of Fertile and Infertile Men: Correlation with Semen Parameters - Khalili, Mohammad Ali; Aghaie-Maybodi, Fatima; Anvari, Morteza; Talebi, Ali Reza (Urology Journal, 2009)
Introduction: Our aim was to compare the nuclear DNA integrity of the spermatozoa from infertile men with abnormal semen parameters with that from normospermic fertile men, and to evaluate the relationship between the sperm DNA integrity and semen parameters. Materials and Methods: Thirty ejaculate samples with abnormal semen analysis and 30 ejaculates with normal semen parameters were randomly collected from infertile and fertile men, respectively. The acridine orange test was used to assess the integrity of sperm DNA. Results: The number of ejaculates with a DNA Fragmentation Index (DFI) above 30% were 16 (53.3%) and 22 (73.3%) in fertile and infertile subjects, respectively (P = .10). The mean DFI was 37.7 ± 19.6% and 46.1 ± 16.7% in the fertile and infertile subjects, respectively (P = .24). The DFI of the fertile men with normal sperm morphology (12 patients) ranged from 1% to 80%. In the samples with oligoasthenospermia, mean DFI was 52.7 ± 17.9%. There were 2 samples with severe teratospermia (normal morphology less than 4%) and DFIs of 70% and 87%. There were no significant correlations between the DNA integrity and the 3 parameters of semen quality in our 60 subjects. Conclusion: Our results failed to show any significant difference in the DNA integrity of the spermatozoa between infertile and fertile men. Also, no correlation was noticed between the DNA abnormality and the semen parameters in the studied samples.